Correction: Antibacterial activity of a dual peptide targeting the Escherichia coli sliding clamp and the ribosome. Issue 4 (6th July 2021) - André, Christophe; Veillard, Florian; Wolff, Philippe; Lobstein, Anne-Marie; Compain, Guillaume; Monsarrat, Clément; Reichhart, Jean-Marc; Burnouf, Dominique Y.; Guichard, Gilles; Wagner, Jérôme E.
Abstract : Correction for 'Antibacterial activity of a dual peptide targeting the Escherichia coli sliding clamp and the ribosome' by Christophe André et al., RSC Chem. Biol., 2020, 1, 137–147, DOI: ; 10.1039/D0CB00060D .